Design and development of augmented reality teaching kit: in TVET learning context - Ismail, Mohd Erfy; Zakaria, Anies Faziehan; Ismail, Irwan Mahazir; Othman, Hasyamuddin; Samsudin, Mohd Ali; Utami, Pipit (Science Publishing Corporation, 2019)
Due to the recent development of computer power and information technology, augmented reality (AR) is commonly found to be one of the interactive experience of a real-world environment refers to the objects are augmented by computer generated information. Previously, there is a number of studies have discussed the importance of AR technologies in various domain, engineering, design. However, it is less focused on integrated the development of AR as a teaching aid kit for specific engineering subjects (Welding Technology). This study proposes a development of AR teaching kit using ADDIE models, which aimed to exhibit required skills for the specific welding technology task. An expert survey is conducted to evaluate the usability of the teaching kit based on the given score. Based on finding shows the positive usability score obtained from the expert validation. This AR teaching kit may facilitate teachers throughout the teaching and learning process.